PENERAPAN VIDEO PROMOSI MENGGUNAKAN APLIKASI FILMORA PADA PETERNAK KAMBING DI MALANG - Mega Mirasaputri Cahyanti; Widi Dewi Ruspitasari; Pipit Rosita Andarsari (Jurnal Pengabdian Masyarakat, 2020)
After Covid-19 attacked Indonesia, many business need to build e new strategy in order to face the new normal era. Including every owner of Goat Farm in Malang, which usually running the buying and selling process traditionally. The new strategy which can be done is through less contact economy, which is using internet. When every owner of goat farm selling their product by internet, they will not also get the usual income earned but also get wider potential buyer in outside Malang. That’s why, Making Promotion Video using Filmora training Activities for Goat Farm in Malang is done in the form of a tutorial delivered directly by the speaker. Where based on the results of this dedication, every owner of Goat Farm in Malang is very interested and eager to participate in similar activities for the development of business knowledge.